Effect of post-partum breeding interval on conception rates in beef cows - Kiracofe, G.H.; Odde, Kenneth G. (Kansas State University. Agricultural Experiment Station, 2011)
We analyzed date on 1536 fall calving Angus cows to determine the effect of post-partum breeding interval on conception rates in beef cows. Normal fertility was observed for cows showing heat 40 or more days post-partum.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Post-partum breeding; Conception rates